Zainteresowanie oraz opłacalność oszczędzania na emeryturę w III filarze - Koćwin, Julitta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The problem presented in the research paper is the issue of retirement savings efficiency in the Third Pillar of social insurance in Poland. The object of accomplished analysis, which constitutes grounds for inference was “the number of accounts in the Third Pillar and the value of accumulated funds”, which allowed defining “interest and attractiveness of the use of financial products offered by the Third Pillar” and “profitability of saving in the Third Pillar”. The results of the research, which determine present interest in saving in the Third Pillar confirm that additional forms of pension security have not reached the desired by the government level of development. Market growth will not occur unless there are financial incentives. Common concerns rouse the role of the state in the Third Pillar, and especially the possibility of taking over accumulated savings by government, as was done with savings accumulated in the Second Pillar (OFE). In this situation, choosing a product of the Third Pillar is a less meaningful issue. It is more important to regularly save money in order to be able to gain from the so called ‘compound interest’, also choosing the right investment strategy and attitude towards risk
Keywords: emerytury; fundusze emerytalne; oszczędzanie; trzeci filar; depozyty bankowe; oszczędności